Manifolds of Eigenfunctions and Potentials of a Family of Periodic Sturm–Liouville Problems - Dymarskii, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider a family of boundary-value problems in which the role of a parameter is played by a potential. We investigate the smooth structure and homotopic properties of the manifolds of eigenfunctions and degenerate potentials corresponding to double eigenvalues.